SMC-Derived Hyaluronan Modulates Vascular SMC Phenotype in Murine Atherosclerosis. Issue 11 (12th November 2021) - Hartmann, Felicia; Gorski, Daniel J.; Newman, Alexandra A.C.; Homann, Susanne; Petz, Anne; Owsiany, Katherine M.; Serbulea, Vlad; Zhou, Yu-Qing; Deaton, Rebecca A.; Bendeck, Michelle; Owens, Gary K.; Fischer, Jens W.
Abstract : Rationale: Plaque instability remains poorly understood and new therapeutic approaches to reduce plaque rupture and subsequent clinical events are of great interest. Recent studies revealed an important role of phenotypic switching of smooth muscle cells (SMC) in controlling plaque stability, including ECM (extracellular matrix) deposition. Objective: The aim of this study was to elucidate the role of hyaluronan derived from SMC–hyaluronan synthase 3 ( Has3 ), in phenotypic switching and plaque stability in an animal model of atherosclerosis. Methods and Results: A mouse line with SMC-specific deletion of Has3 and simultaneous SMC-lineage tracing ( e YFP [enhanced yellow fluorescent protein]) on an Apoe −/− background was used. Lineage tracing of SMC with e YFP revealed that SMC-specific deletion of Has3 significantly increased the number of LGALS3 + (galectin-3) transition state SMC and decreased ACTA2 + (alpha-smooth muscle actin) SMC. Notably, SMC- Has3 deletion led to significantly increased collagen deposition and maturation within the fibrous cap and the whole lesion, as evidenced by picrosirius red staining and LC-PolScope analysis. Single-cell RNA sequencing of brachiocephalic artery lesions demonstrated that the loss of SMC- Has3 enhanced the transition of SMC to a Lgals3 +, ECM-producing phenotype with elevated acute-phase response gene expression. Experiments using cultured murine aortic SMC revealed that blocking CD44 (cluster of differentiation-44), an important hyaluronan binding receptor, recapitulated the enhanced acute-phase response, and synthesis of fibrous ECM. Conclusions: These studies provide evidence that the deletion of SMC- Has3 results in an ECM-producing transition state SMC phenotype (characterized by LGALS3 + expression), likely via reduced CD44 signaling, resulting in increased collagen formation and maturation, an index consistent with increased plaque stability. Abstract : Supplemental Digital Content is available in the text.